The peripheral vascular responses in non‐freezing cold injury and matched controls. Issue 3 (19th February 2023) - Eglin, Clare M.; Wright, Jennifer; Maley, Matthew J.; Hollis, Sarah; Massey, Heather; Montgomery, Hugh; Tipton, Michael J.
Abstract : New Findings: What is the central question of this study? Does non‐freezing cold injury (NFCI) alter normal peripheral vascular function? What is the main finding and its importance? Individuals with NFCI were more cold sensitive (rewarmed more slowly and felt more discomfort) than controls. Vascular tests indicated that extremity endothelial function was preserved with NFCI and that sympathetic vasoconstrictor response might be reduced. The pathophysiology underpinning the cold sensitivity associated with NFCI thus remains to be identified. Abstract: The impact of non‐freezing cold injury (NFCI) on peripheral vascular function was investigated. Individuals with NFCI (NFCI group) and closely matched controls with either similar (COLD group) or limited (CON group) previous cold exposure were compared ( n  = 16). Peripheral cutaneous vascular responses to deep inspiration (DI), occlusion (PORH), local cutaneous heating (LH) and iontophoresis of acetylcholine and sodium nitroprusside were investigated. The responses to a cold sensitivity test (CST) involving immersion of a foot in 15°C water for 2 min followed by spontaneous rewarming, and a foot cooling protocol (footplate cooled from 34°C to 15°C), were also examined. The vasoconstrictor response to DI was lower in NFCI compared to CON (toe: 73 (28)% vs. 91 (17)%; P  = 0.003). The responses to PORH, LH and iontophoresis were not reduced compared to either COLD or CON. During the CST, toe skin temperature rewarmed more slowly in NFCI than COLD or CON (10 min: 27.4 (2.3)°C vs. 30.7 (3.7)°C and 31.7 (3.9)°C, P  < 0.05, respectively); however, no differences were observed during the footplate cooling. NFCI were more cold‐intolerant ( P  < 0.0001) and reported colder and more uncomfortable feet during the CST and footplate cooling than COLD and CON ( P  < 0.05). NFCI showed a decreased sensitivity to sympathetic vasoconstrictor activation than CON and greater cold sensitivity (CST) compared to COLD and CON. None of the other vascular function tests indicated endothelial dysfunction. However, NFCI perceived their extremities to be colder and more uncomfortable/painful than the controls.